Auswirkungen der »Verursacherarchäologie« auf den Kenntnisstand zu eisenzeitlichen Siedlungen in Schleswig-Holstein - Lütjens, Ingo (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
The first developer funded excavations were carried out in Schleswig-Holstein in 2004. Since 2012, the so-called »Verursacherprinzip « has been included in the law (»Denkmalschutzgesetz«). These investigations showed that previously unknown Iron Age settlements were relatively often recorded. This led to a considerable gain of knowledge, especially for the eastern and central parts of the country. Prior to 2012, Iron Age settlements were rarely uncovered on a large scale but were mainly excavated as research projects in the West Coast regions. This article presents the changed level of knowledge and the resulting potential.